The Emerging Role of the Chief Research Informatics Officer in Academic Health Centers - Sanchez-Pinto, L. Nelson (Appl Clin Inform, 2017)
Background : The role of the Chief Research Informatics Officer (CRIO) is emerging in academic health centers to address the challenges clinical researchers face in the increasingly digitalized, data-intensive healthcare system. Most current CRIOs are the first officers in their institutions to hold that role. To date there is very little published information about this role and the individuals who serve it. Objective : To increase our understanding of the CRIO role, the leaders who serve it, and the factors associated with their success in their organizations. Methods : The Clinical Research Informatics Working Group of the American Medical Informatics Association (AMIA) conducted a national survey of CRIOs in the United States and convened an expert panel of CRIOs to discuss their experience during the 2016 AMIA Annual Symposium. Results : CRIOs come from diverse academic backgrounds. Most have advance training and extensive experience in biomedical informatics but the majority have been CRIOs for less than three years. CRIOs identify funding, data governance, and advancing data analytics as their major challenges. Conclusion : CRIOs play an important role in helping shape the future of clinical research, innovation, and data analytics in healthcare in their organizations. They share many of the same challenges and see the same opportunities for the future of the field. Better understanding the background and experience of current CRIOs can help define and develop the role in other organizations and enhance their influence in the field of research informatics. Citation: Sanchez-Pinto LN, Mosa ASM, Fultz-Hollis K, Tachinardi U, Barnett WK, Embi PJ. The Emerging Role of the Chief Research Informatics Officer in Academic Health Centers. Appl Clin Inform 2017; 8: 845–853 https://doi.org/10.4338/ACI-2017-04-RA-0062